Agricultural markets mechanisms, failures, and regulations - Martimort, David (Contributions to economic analysis ;, 1996)
This volume aims at covering the variety of issues lying at the intersection of the modern theory of Industrial Organization and of the more traditional Agricultural Economics. The book is divided into three main sections. Each of them includes contributions which are particularly relevant for a better understanding of one or several of the following key issues: the organization of agriculture and its mechanisms, the extent of the market power in agri-food industries and, more generally, the failures of agricultural markets, and finally the nature of government's intervention in these markets.